TOTAL ANTIOXIDANT, RENAL FUNCTION TEST IN IRAQI WOMEN WITH BREAST CANCER (World Bulletin of Public Health, 2022)
Cancer is a collection of disorders characterized by uncontrolled cell growth, with breast cancer being the most common among women. The purpose of this study is to look at renal function and total antioxidants in Iraqi women who have been diagnosed with breast cancer. Three groups of Iraqi women were chosen: group I (50 healthy women), group II (32 new patients diagnosed with breast cancer but not getting chemotherapy), and group III (43 patients who received chemotherapy). The study has included the measurement of two biochemical variables, including total antioxidant and renal function tests. The results showed a significant decrease in creatinine between groups I and III. The results also showed a significant increase (P
Keywords: antioxidants; breast cancer; renal function test; Statistical analysis